[Uzi ; Cuisine ; To save the people [videorecording] - Lazaro, Cheche (The Probe Team, 1989)
A controversy about illegal importation of guns by Congressmen. Focuses in the educational system and philosophy behind the kind of training young medical students. A feature on two young rich and educated women who have chosen the kitchen as their place of work.